The biological activity of Moringa oleifera seeds extracts against Candida yeast - Shrook Gany Yassin, (American Journal of Biomedicine and Pharmacy, 2026)
This study was conducted at the Open Educational College Science Laboratory from February to May 2026 to evaluate and compare the efficacy of alcoholic and aqueous extracts of Moringa oleifera seeds as biological agents two Candida species: Candida albicans and Candida glabrata. The results showed that both extracts (alcoholic and aqueous) The alcoholic extract resulted in an inhibition zone diameter of 14.944 mm for Candida albicans compared to 11.378 mm for Candida gilberata. The aqueous extract resulted in an inhibition zone diameter of 8.672 mm for Candida albicans and 6.911 mm for Candida gilberata exhibited biological activity that inhibited Candida yeast growth, with the alcoholic extract demonstrating significantly superior efficacy at all tested concentrations. The Candida strains also showed varying sensitivity to the extracts, with Candida albicans exhibiting greater sensitivity compared to Candida glabrata, which displayed higher resistance. GC-MS analysis of the alcoholic extract of Moringa seeds revealed the presence of biologically active compounds, such as phytosterols, long-chain fatty acids, and squalene, which are likely responsible for the antifungal activity, in addition to their antioxidant and anti-inflammatory properties. These results indicate that Moringa oleifera seeds possess antifungal biological activity, making them a potential natural source of antifungal compounds, particularly against certain strains of Candida.